RHETORICAL CULTURE OF TEACHER TECHNICAL UNIVERSITY: STRUCTURAL FEATURES - Zaljubivsjka, Oksana B. (Educological discourse, 2014)
This article presents the development of structural meaning of rhetorical culture of teacher Technical University. The structure is due to use of cultural, regulatory, technological, educational, humanistic, value approach in determining the rhetorical culture of teachers Technical University. Author moving away from the structuring of rhetorical culture according to the stages of rhetorical activity, and provides structure of  rhetorical culture for functional aspects, so each structural component permeates all stages of professional rhetorical activity. The structure of rhetorical culture of teacher Technical University was identified four components: motivational-value, intellectual-creative, verbal-stylistic, personality-performing; each of the components fleshed out by several essential characteristics.